(untitled) (Journal of actual problems of jurisprudence, 2019)
This article covers the legal issues of countering terrorism and extremism in the Republic of Kazakhstan. It is noted that terrorism and extremism in any form of its manifestations have become one of the most dangerous problems of our time and represent a potential threat to the national security of the country. It is impossible to eradicate the danger and threat of terrorism and extremism by force and prohibitive measures alone. Priority should be given to preventive and preventive measures. At the same time, the main focus should be shifted to active joint activities of the state and civil society. Terrorism and extremism can be qualified as active actions prohibited by law due to the fact that they cause significant harm and pose a danger to the individual, society and the state as a whole. This action combines the objects to which these actions are directed. These are government agencies, power structures, and the nature of these actions associated with violence. At the same time, terrorism is characterized by methods of intimidation of the population and is aimed at causing damage to the individual, society and the state. At the same time, extremism can be qualified as a manifestation of adherence to extreme views and, in particular, extreme measures. The author proposes changes and additions to the law «On Countering Terrorism». Thus, it is proposed to supplement this law with the concept of «international terrorism». It is proposed to conduct a full analysis of the current laws, which in one way or another regulate actions to prevent and counter terrorism and extremism. The question is raised about the possible development of the Anti-Terrorism Code of the Republic of Kazakhstan. It is also proposed to regulate by law issues related to the compensation of property damage as a result of an act of terrorism, as well as compensation for harm to individuals and legal entities caused by the suppression of an act of terrorism. Key words: state, terrorism, extremism, counteraction, violence, protection of human rights, law.